2018
DOI: 10.3390/molecules23113009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pentacyclic Triterpenoids-Rich Callus Extract of Chaenomeles japonica (Thunb.) Lindl. ex Spach on Viability, Morphology, and Proliferation of Normal Human Skin Fibroblasts

Abstract: The effect of the well-characterized callus extract of Chaenomeles japonica on viability, morphology, and proliferation of normal human skin fibroblasts was investigated. The phytochemical analysis was performed using the ultra-high performance liquid chromatography method. The total phenolic, phenolic acid, and flavonoid contents were determined spectrophotometrically. The antioxidant activity was investigated using the DPPH (1,1-Diphenyl-1-picrylhydrazyl Radical Scavenging), FRAP (Ferric Reducing Antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Chun et al [ 46 ] demonstrated the antiproliferative properties of Chaenomeles sinensis fruit extract against HepG2 cells. Kikowska et al [ 47 ] noticed that callus extract of Chaenomeles japonica decreased the proliferation of normal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chun et al [ 46 ] demonstrated the antiproliferative properties of Chaenomeles sinensis fruit extract against HepG2 cells. Kikowska et al [ 47 ] noticed that callus extract of Chaenomeles japonica decreased the proliferation of normal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry revealed apoptosis and necrosis in HT-29 cells. Kikowska et al [ 47 ] investigated the effect of callus extract of C. japonica on themorphology of normal human skin fibroblasts. At a lower concentration (12.5 µg/mL), no differences were observed compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenolic composition of calli is often low in flavonoid compounds and relatively high in phenolic acids. In the triterpenoid-compound-producing species, such as Chaenomeles japonica , several types of callus investigated by Kikowska et al [ 34 ] were similarly more abundant in phenolic acids than in flavonoids. The callus line containing the least polyphenols was especially high in pentacyclic triterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…The media variants for callus initiation and proliferation were initially tested and the four callus lines with the best growth indexes were selected for the further investigations (according to the paper [16]). Briefly, callus was inducted on young leaves (blades and petioles) of micropropagated plantlets.…”
Section: Plant Materialsmentioning
confidence: 99%